Sterilizable vertical n-type organic electrochemical transistors for skin-conformal ECG monitoring - Kim, Ji Hwan; Lee, Inho; Lee, Won June; Shin, Dongjoon; Lee, Hyeongbeom; Flagg, Lucas Q.; Chaudhary, Jagrity; You, Liyan; Kang, Keehoon; Mei, Jianguo; Park, Sungjun (Materials Science and Engineering R: Reports, 2025)
The development of stable, high-performance epidermal biosignal monitoring devices is critical for advancing wearable healthcare technologies. Here, we present a novel electrochemical transistor-based biosignal sensor utilizing a 4-terminal vertical Corbino configuration and an n-doped poly(benzodifurandione) (n-PBDF) polymer. The 4-terminal device configuration effectively reduces the parasitic resistance, enabling a high transconductance of 374 mS at a low operational voltage, and one of the highest reported μC* values of 1787 F cm−1 V−1 s−1 for n-type OECTs. In addition, this device achieves exceptional operational stability, maintaining consistent performance over extended periods, and demonstrates a superior shelf-life stability under ambient conditions. Furthermore, the sensor exhibits robust sterilization capabilities, withstanding both UV and thermal sterilization processes without performance degradation. Mechanical flexibility, a key requirement for on-skin applications, is ensured by the intrinsic properties of the n-PBDF polymer and the ultra-thin device architecture. The combination of these features makes this device an ideal candidate for monitoring of biosignals such as electrocardiograms, addressing practical challenges in wearable biosensing technologies.
Keywords: Biosignals; Durable electrocardiogram sensor; Integrated device; Mixed ionic-electronic conductors; N-doped; N-doped poly(benzodifurandione); Organic electrochemical transistors; Organic mixed ionic–electronic conductor; Organics; Vertically integrated device; Durable electrocardiogram sensor; n-doped poly(benzodifurandione); Organic electrochemical transistor; Organic mixed ionic–electronic conductor; Vertically integrated device